Reading and Writing on Reading and Writing: Short Poetry on Flyleaves in a Manuscript of the Metrical Grammar (DCA 00065) - Pritula, Anton Dmitrievič (Scrinium, 2021)
The short pieces discussed in the paper were added between larger texts and on the flyleaves by the scribe himself. Thematically, the poems may be divided in two blocks: the first one contains poems on reading, studying grammar, and on the scribal activities, whereas the second one comprises poetry ascribed to Bar ʿEbrōyō on different topics. The manuscript under discussion – Bar ʿEbrōyō’s (1226–1286) Metrical Grammar (DCA 00065) – was written in 1552 by ʿAbdīšōʿ of Gāzartā, an East Syrian patriarch (1555–1570), poet and copyist. These small pieces forming short verse collections illustrate the complex processes that took place in the manuscript circulation and literary life during the Early Ottoman period. All the short poems were never published or studied before, and for that reason they are placed here in the Appendix in both Syriac original and English translation.